Kajian Penyebab Rembesan pada Bendungan Situ Lembang di Kabupaten Bandung Barat - Apip, Deni Saepul; Soenarto, Bambang (Universitas Batanghari Jambi, 2024)
A dam is a construction structure built to hold back the flow of water from upstream to downstream. Geographically, the Situ Lembang Dam is located in Kertawangi Village, Cisarua District, West Bandung Regency, the Situ Lembang Dam has a length of 350 m. One of the problems with dams is seepage. Seepage is defined as the property of a porous material that allows fluid in the form of water to flow through the pore cavity. The aim of this research is to determine the effect of variations in hydrostatic height on seepage that occurs in the dam body. The material forming the dam body is a type of organic clay. Almost all of the instrumentation equipment at 'Situ Lembang' no longer functions. This research uses laboratory simulations to review seepage patterns and seepage discharge against variations in hydrostatic height. Seepage discharge (Qf) is calculated using 3 methods, namely the Dupuit method, Schaffernak method, and Cassagrande method. The hydrostatic height variations reviewed are H10, H15, and H20.